Efektivitas Promosi Kesehatan Permainan Ular Tangga Modifikasi terhadap Tingkat Pengetahuan tentang Protokol Kesehatan COVID-19 - Enisah Maksum; Nurharlina Nurharlina; Dyan K. Nugrahaeni; Iin Inayah; Mamat Lukman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to test the effectiveness of the modified snake and ladder game on the level of knowledge about COVID-19 health protocols in grade 1 elementary school (SD) students at SDN Karang Pawulang, Bandung City. The method used is a true experiment pre-test & post-test group control design. The results showed a difference between the pre-test and post-test scores obtained was 0.025. In conclusion, the modified snake and ladder game is effective in increasing the knowledge of grade 1 elementary school students about the COVID-19 health protocol. Keywords: COVID-19, Health Promotion, Health Protocol, Knowledge Level, Snakes and Ladders